Ethical Considerations Associated with Closing a Non-communicable Disease Program in a Humanitarian Setting - Saeed, Handreen; Schwartz, Lisa; Hunt, Matthew (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
Managing non-communicable diseases (NCDs) in crisis-affected and fragile humanitarian contexts requires special attention because primary health care systems often collapse or become compromised in such settings. As a result, addressing and managing these diseases become more challenging. Humanitarian organizations that intervene in crisis situations are increasingly including NCD management in the services they support and provide; however, they encounter a range of issues such as ensuring the quality of care, sustainability of programs, and the possibility of unintended harms. This case study explores ethical considerations raised by a mobile NCD program run by an international humanitarian organization in a country affected by a protracted civil war.